Outside Front Cover: Biotechnology Journal 9/2019. Issue 9 (2nd September 2019) - Guirimand, Gregory G. Y.; Bamba, Takahiro; Matsuda, Mami; Inokuma, Kentaro; Morita, Kenta; Kitada, Yuki; Kobayashi, Yuma; Yukawa, Takahiro; Sasaki, Kengo; Ogino, Chiaki; Hasunuma, Tomohisa; Kondo, Akihiko
Abstract : Xylitol, a major pentose alcohol sugar, is produced from lignocellulosic biomass by a recombinant strain of Saccharomyces cerevisiae, expressing cytosolic xylose reductase (SsXR), along with homologous maltose transporter (ScMAL11) and β‐glucosidase (AaBGL) displayed on the cell surface. This recombinant strain is able to efficiently co‐utilize cellobiose and xylose and produce xylitol. This is reported by Gregory G. Y. Guirimand, Takahiro Bamba, Mami Matsuda, Kentaro Inokuma, Kenta Morita, Yuki Kitada, Yuma Kobayashi, Takahiro Yukawa, Kengo Sasaki, Chiaki Ogino, Tomohisa Hasunuma, and Akihiko Kondo in article1800704 .